The composition and structure of the plankton community in the Tudor Creek, Mombasa, Kenya. - Okemwa, E.N. (Unknown, 1988)
This study was undertaken with a view to describing the species composition and the community structure of copepods in the Tudor Creek, Mombasa, Kenya. The first quantative study of the pelagic zooplankton community of the Tudor Creek was undertaken from December 1984 to December 1987. Between December and March 1985 a Bongo plankton net of. 335 IWl mesh size was used from the vessel "R.V. Maumba". From April 1985 to December 1987 a conical plankton net was used from a small canoe equipped with an outboord engine. The net, with a mesh aperture size of 335 1Wl, a length of 1 m, and 45 cm in diameter at the mouth, was fitted with a flow meter at the mouth. Surface plankton samples were taken from September 1985 to August 1986 using a small canoe at each of five permanent stations during day- and night-time, at one neap and one spring tide each month. Thereafter only day-time neap and spring tide samples were taken from September 1986 to December 1987 at the five stations. 24houres cycle sampling was occasionally done at stations 1 and 5 simultaneously. Results from the study shows that zooplankton are rich and abundant. Over 51 taxa were recorded. Close to 74 % of the zooplankton comprised copepods of which the most important were calanoids followed by cyclopoids, poecilostomatoids, harpacticoids and monstrilloids. The most commonly encountered calanoid species were Centropages orsinii, Acrocalanus lon icornis, Clausocalanus tarrani, Temora turbinata, Paracalanus aculeatis, P. simplex, Canthocalanus pauper, Undinula vulgaris, Acartia danae, Euchaeta marina and Eucalanus spp.
Date of Publication may not be correct.